The Standard Days Method (R) : Efficacy, satisfaction and demand at regular family planning service delivery settings in Turkey - (:unkn) unknown (TAYLOR & FRANCIS LTD, 2014)
Objectives To evaluate the demand, efficacy, and satisfaction concerning the Standard Days Method (R) (SDM; a fertility awareness method) as an option presented among other contraceptive methods at regular service delivery settings. Methods The survey group consisted of 993 women who presented at the primary care units in Umraniye District of Istanbul, Turkey, between 1 October 2006 and 31 March 2008, and started to use a new method. Women were enrolled until reaching a limit of 250 new users for each method, or expiration of the six-month registration period. Participants were followed for up to one year of method use. Results The characteristics of women who chose the SDM were similar to those of participants who opted for other methods. The most common reasons for selecting it were that it is natural and causes no side effects. Fifty-one percent used the SDM for the full year, compared to 71% who chose an intrauterine device (IUD). Continuation rates were significantly lower for all other methods. During the one-year follow-up period, 12% of SDM-, 7% of pill-, 7% of condom-, 3% of monthly injection-, 1% of quarterly injection-, and 0.5% of IUD users became pregnant. Conclusion The SDM had relatively high continuation rates and relatively good levels of satisfaction among participants and their husbands. It should be mentioned among the routinely offered contraceptive methods.
Keywords: Efficacy; CycleBeads (R); Standard Days Method; Satisfaction; Contraceptive counselling; Contraceptive continuation; Turkey